Immunoadsorption of Agonistic Autoantibodies Against α1‐Adrenergic Receptors in Patients With Mild to Moderate Dementia. Issue 5 (20th April 2016) - Hempel, Petra; Heinig, Bente; Jerosch, Carola; Decius, Imke; Karczewski, Peter; Kassner, Ursula; Kunze, Rudolf; Steinhagen‐Thiessen, Elisabeth; Bimmler, Marion
Abstract: Dementia has been shown to be associated with agonistic autoantibodies. The deleterious action of autoantibodies on the α1‐adrenergic receptor for brain vasculature has been demonstrated in animal studies. In the current study, 169 patients with dementia were screened for the presence of agonistic autoantibodies. 47% of patients suffering from mild to moderate Alzheimer's disease and/or vascular dementia carried these autoantibodies. Eight patients positive for autoantibodies underwent immunoadsorption. Patients treated on four consecutive days were subsequently negative for autoantibodies and displayed stabilization of cognitive and mental condition during 12–18 months' follow‐up. In patients treated for 2–3 days, autoantibodies were reduced by only 78%. They suffered a rebound of autoantibodies during follow‐up, benefited from immunoadsorption too, but their mental parameters worsened. We provide first data on the clinical relevance of agonistic autoantibodies in dementia and show that immunoadsorption is safe and efficient in removing autoantibodies with overall benefits for patients.